Analisis Spasial Pengembangan Daya Tarik Wisata Berbasis Sistem Informasi Geografis di Desa Manikyang Kecamatan Selemadeg Kabupaten Tabanan - Siddiqoh, Fiki Aisyah; Sardiana, I Ketut; Adi, I Gusti Putu Ratna (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024)DO - 10.24843/AJoAS.2024.v14.i01.p06, 2024)
Spatial Analysis of the Development of Tourist Attractions Based on Geography Information System in Manikyang Village Selemadeg District Tabanan Regency. Tourist attraction is everything that has a unique attraction, interesting, high value, which can be the reason tourists in visiting a location. Manikyang village has unmanaged tourism potential, tourism potential development has not been maximized, lack of utilization, management of natural resources and human resources so it has not been able to provide economic benefits for the community. Based on these problems can be done the development of tourist attraction with spatial analysis based on Geographic Information System. The system performs tourist attraction analysis using spatial-based data and information. This study aims to identify the type and distribution of tourist attractions and analyze the direction of tourism attraction development in Manikyang Village. The method used is spatial analysis based on land use type, tourist attraction location point, facilities, and accession. Results of spatial data processing and field survey show that Manikyang Village has 6 natural tourism potentials, 4 artificial tourism potentials, and 3 cultural/religious tourism potentials spread across 5 banjar villages. The results showed that Manikyang Village is suitable to be developed as a tourism themed Ecotourism and Religious Tourism with the tourism attraction development zone divided into a core zone covering an area of 19 ha (6.17%), a buffer zone covering an area of 277.38 ha (90.06%), and a support zone of 11.62 ha (3.77%).